physicscatalyst.com logo




Chapter 2 Inverse Trigonometric Functions Exercise 2.2




In this page we have Class 12 Maths NCERT Solutions Chapter 2 Inverse Trigonometric Functions for EXERCISE 2.2 . Hope you like them and do not forget to like , social share and comment at the end of the page.

Important Formula’s
Class 12 Maths NCERT Solutions Chapter 2 Inverse Trigonometric Functions Exercise 2.2
Class 12 Maths NCERT Solutions Chapter 2 Inverse Trigonometric Functions Exercise 2.2

Prove the following



Question 1. $3 \sin ^{-1} = \sin ^{-1}(3x - 4x^{3}) , \; x \in \left [ -\frac{1}{2}, \frac{1}{2} \right ]$
Solution
Let sin-1x = y, then x = sin y
We get,
RHS = $\sin ^{-1} (3x - 4x^{3 }) = \sin ^{-1} (3 \sin y - 4 \sin^{3} y )\\$
$= \\\sin ^{-1} (\sin 3 y) = 3 y = 3 \sin^{-1}x$
= LHS

Question 2. $3 \cos ^{-1} x = cos ^{-1}(4x^{3} - 3x), x \in \left [ \frac{1}{2}, 1 \right ]$
Solution
Let cos-1 x = y, then x = cos y
We get,
RHS = $\cos ^{-1} (4x^{3} - 3x) = cos^{-1}(4cos^{3} y - 3cos y)$
$= \\\cos ^{-1} (cos 3 y ) = 3 y = 3 cos^{-1} x$
= LHS
 

Question 3. Show that $tan ^{-1} \frac{2}{11} + \tan ^{-1} \frac{7}{24} = \tan ^{-1} \frac{1}{2}$
Solution
LHS = $tan ^{-1} \frac{2}{11} + \tan ^{-1} \frac{7}{24} $
$= tan ^{-1} \left ( \frac{\frac{2}{11} + \frac{7}{24}}{1 - \frac{2}{11} \times \frac{7}{24}} \right ) = \tan^{-1} \left (\frac{\frac{48 + 77}{11 \times 24}}{\frac{11 \times 24 - 14}{11 \times 24}} \right )\\$
$\\= tan ^{-1} \frac{48 + 77}{264 - 14} = \tan^{-1} \frac{125}{251} = \tan^{-1} \frac{1}{2}$ = RHS
 

Question 4. Show that $2 \tan^{-1} \frac{1}{2} + \tan^{-1}\frac{1}{7} = \tan^{-1}\frac{31}{17}$
Solution
LHS = $2 \tan^{-1} \frac{1}{2} + \tan^{-1}\frac{1}{7} $
$= \tan^{-1} \left [ \frac{2 \times \frac{1}{2}}{1 - \left ( \frac{1}{2} \right )^{2}} \right ] + \tan ^{-1} \frac{1}{7} = \tan ^{-1} \frac{1}{\left ( \frac{3}{4} \right )} + \tan^{-1} \frac{1}{7}\\$
$\\= \tan^{-1} \frac{4}{3} + \tan^{-1} \frac{1}{7} = \tan^{-1}\left ( \frac{\frac{4}{3} + \frac{1}{7}}{1 - \frac{4}{3} \times \frac{1}{7}} \right )\\$
$\\= \tan^{-1} \left ( \frac{\frac{28 + 3}{3 \times 7}}{\frac{3 \times 7 -4}{3 \times 7}} \right ) = \tan^{-1} \frac{28 + 3}{21 - 4} = tan^{-1} \frac{31}{17} = RHS$  

Write the following functions in the simplest form


Question 5. $\tan^{-1}\frac{\sqrt{1 + x^{2}} - 1}{x}, \; x \neq 0$
Solution
Let x = tan y
$ = \tan^{-1}\frac{\sqrt{1 + x^{2}} - 1}{a}$ = $\tan^{-1} \frac{\sqrt{1 + \tan^{2}y } - 1}{\tan y } \\$
$\\ = \tan^{-1} \left ( \frac{ \sec y - 1 }{\tan y } \right ) = \tan^{-1} \left ( \frac{1 - \cos y }{\sin y } \right )\\$
$\\\tan^{-1} \left ( \frac{2\sin^{2}\frac{y }{2}}{2\sin\frac{y }{2}\cos\frac{y }{2}}\right ) = \tan^{-1}\left ( \tan \frac{y }{2} \right )\\$
$\\= \frac{y }{2} = \frac{1}{2}\tan^{-1}x$  

Question 6. $\tan^{-1}\frac{1}{\sqrt{x^{2}-1}}$, |x|> 1
Solution:
Let x = csc y
$\tan^{-1}\frac{1}{\sqrt{x^{2}-1}} = \tan^{-1}\frac{1}{\sqrt{\csc^{2}y -1}} $
$=\tan^{-1}\frac{1}{ \cot y } = \tan^{-1} \tan y = y = \csc ^{-1}x $
$= \frac{\pi}{2} - sec^{-1}x$
 

Question 7. $\tan^{-1} \left ( \sqrt{\frac{1 - \cos x}{1 + \cos x}} \right ), x < \pi,$
Solution
$\tan^{-1} \left ( \sqrt{\frac{1 - \cos x}{1 + \cos x}} \right ) = \tan^{-1} \left ( \sqrt{\frac{2 \sin^{2}\frac{x}{2}}{2 \cos^{2}\frac{x}{2}}} \right ) \\$
$=\\\tan^{-1} \left ( \sqrt{\tan^{2}\frac{x}{2}} \right ) = \tan^{-1}\left ( \tan \frac{x}{2} \right ) = \frac{x}{2}$  

Question 8. $\tan^{-1} \left ( \frac{\cos x - \sin x}{\cos x + \sin x} \right ), 0 < x < \pi$
Solution
$ \tan^{-1} \left ( \frac{\cos x - \sin x}{\cos x + \sin x} \right ) = \tan^{-1} \left ( \frac{1 - \frac{\sin x}{\cos x}}{1 + \frac{\sin x}{\cos x}} \right ) = \tan^{-1} \left ( \frac{1 - \tan x}{1 + \tan x} \right )\\$
$=\\\tan^{-1} \left ( \frac{1 - \tan x}{1 + 1.\tan x} \right ) = \tan^{-1} \left ( \frac{\tan \frac{\pi}{4} - \tan x}{1 + \tan \frac{\pi}{4}.\tan x}\right )\\$
$=\\\tan^{-1} \left [ \tan \left ( \frac{\pi}{4} - x \right )\right ] = \frac{\pi}{4} - x$
 
 

Question 9: $\tan^{-1} \frac{a}{\sqrt{x^{2} - a^{2}}}, \left | a \right | < x$
Solution
Let a = x sin y
$\tan^{-1} \frac{a}{\sqrt{x^{2} - a^{2}}} = \tan^{-1} \left ( \frac{x\sin y }{\sqrt{x^{2} - x^{2}\sin^{2}y }} \right ) = \tan^{-1}\left ( \frac{x\sin y }{x \sqrt{1 - \sin^{2}y }} \right ) \\$
$=\\\tan^{-1} \left ( \frac{x \sin y }{x \sin y} \right ) = tan ^{-1} (\tan y ) = y = \sin ^{-1} \frac{a}{x}$
 



Question 10.: $\tan^{-1} \left ( \frac{3x^{2}a - a^{3}}{x^{3} - 3xa^{2}} \right ) , x > 0; \frac{-x}{\sqrt{3}} \leq a\frac{x}{\sqrt{3}}$
Solution
Let a = x tan y
$\tan^{-1} \left ( \frac{3x^{2}a - a^{3}}{x^{3} - 3xa^{2}} \right ) = \tan^{-1} \left ( \frac{3x^{2}.x \tan y - x^{3}\tan^{3}y }{x^{3} - 3x.x^{2}\tan^{2}y } \right ) \\$
$=\\\tan^{-1} \left ( \frac{3x^{3} \tan y - x^{3}\tan^{3}y }{x^{3} - 3x^{3}\tan^{2}y } \right ) = \tan^{-1} \left ( \frac{3 \tan y - \tan^{3}y}{1 - 3\tan^{2}y } \right ) \\$
$=\tan^{-1} \left ( \tan 3 y \right ) = 3 y = 3 tan ^{-1} \frac{a}{x}$
 

Find the values of each of the following


Question 11. Solve $\tan^{-1}\left [ 2\cos \left ( 2 \sin^{-1} \frac{1}{2} \right ) \right ]$
Solution
$\tan^{-1}\left [ 2\cos \left ( 2 \sin^{-1} \frac{1}{2} \right ) \right ] = \tan^{-1}\left [ 2\cos \left ( 2 \sin^{-1} \left ( \sin \frac{\pi}{6} \right ) \right ) \right ] \\$
$=\\\tan^{-1}\left [ 2\cos \left ( 2 \times \frac{\pi}{6} \right ) \right ] = \tan^{-1} \left [ 2 \cos \left ( \frac{\pi}{3} \right ) \right ] = \tan^{-1} \left [ 2 \times \frac{1}{2} \right ]\\$
$=\tan^{-1}\left [ 1 \right ] = \frac{\pi}{4}$
 

Question 12. Solve $\cot \left (\tan^{-1} a + \cot ^{-1} a \right )$
Solution
$\cot \left (\tan^{-1} a + \cot ^{-1} a \right ) = \cot \left( \frac{\pi}{2} \right)$ = 0
 

Find the values of each of the expressions in Exercises 16 to 18.


Question 16 sin-1(sin 2π/3)
Solution
sin-1 (sin 2π/3)
Now We know that sin-1 (sin x) = x if x in [π/2, -π/2], which is the principal value branch of sin-1 x.
Now 2π/3 is not in [π/2, -π/2],So
= sin-1 [(sin π - 2π/3)]
= sin-1 [sin (π/3)]
= π/3

Question 17 tan-1 (tan 3π/4)
Solution
tan-1(tan 3π/4)
= tan-1 [tan (3π/4)]
= tan-1 [tan (π - π/4)]
= tan-1 [-tan (π/4)]
= tan-1 [ -tan (π/4)]
= -π/4

Question 18 tan [sin-1 (3/5) + cot-1 (3/2) ]
Solution
let x=sin-1 (3/5), sinx= 3/5 , cos x=(1-sin2x)1/2= 4/5
So tanx=3/4
or x=tan-1 (3/4)
Now cot-1 (3/2) = tan-1 (2/3)
So
tan [sin-1 (3/5) + cot-1 (3/2) ]
=tan [tan-1 (2/3) + tan-1 (2/3) ]
=tan [tan-1 (17/6)] =17/6

Question 19 cos-1 [cos (7π/6)] is equal to
(A) 7π/6
(B) 5π/6
(C) π/3
(D) π/6
Solution
= cos-1 [cos (2π - 5π/6)]
= cos-1 [cos (5π/6)]
= 5π/6
Hence the correct option is (B)

Question 20 sin [(π/3) - sin-1 (-1/2)] is equal to
(A) 1/2
(B) 1/3
(C) 1/4
(D) 1
Solution
sin [(π/3) - sin-1 (-1/2)]
=sin [(π/3) - sin-1 sin (-π/6)]
=sin [(π/3) +(π/6) ]
=sin (π/2)
=1
Hence the correct option is (D)

Question 21 tan-1 √3 - cot-1 (-√3) is equal to
(A) π
(B) -π/2
(C) 0
(D) 2√3
Solution
tan-1 √3 =x
or tan (x) =√3
or x= π/3( Principle Range)

cot-1 (-√3) =y
or cot y= -√3
or y = 5π/6 ( Principle Range)

tan-1 √3 - cot-1 (-√3)
= π/3 - 5π/6
=-π/2
Hence the correct option is (B)

Related Topics


link to this page by copying the following text


Go back to Class 12 Main Page using below links
Class 12 Maths Class 12 Physics Class 12 Chemistry Class 12 Biology





Note to our visitors :-

Thanks for visiting our website.
DISCLOSURE: THIS PAGE MAY CONTAIN AFFILIATE LINKS, MEANING I GET A COMMISSION IF YOU DECIDE TO MAKE A PURCHASE THROUGH MY LINKS, AT NO COST TO YOU. PLEASE READ MY DISCLOSURE FOR MORE INFO.